Strategi Komunikasi Keluarga TNI saat Menjalani Long Distance Marriage dalam Mempertahankan Keharmonisan (Studi Kasus: Kopasgat Unifil PBB di Lebanon) - Shofiatun Nisa; Sudaryono Sudaryono; Fauzan Ammari Sholihin (Asosiasi Dosen Muda Indonesia, 2026)
This study aims to determine the communication strategies used by Indonesian National Armed Forces (TNI) families to maintain household harmony during long-distance marriages (LDM), particularly among KOPASGAT soldiers serving in the UN UNIFIL mission in Lebanon. Furthermore, this study explores the factors influencing successful communication and the obstacles that arise in long-distance relationships. This study uses a qualitative approach with a case study method. Data were obtained through in-depth interviews with five TNI KOPASGAT UNIFIL FBB soldiers in Lebanon as key informants, five wives, two children aged at least 10 years, and one expert informant in the field of family psychology. The theories used in this study are Family Systems Theory and The Interactional View. The results show that the communication strategies implemented emphasize openness, consistent communication, emotional support, and the use of digital technology. Factors supporting successful communication include trust, commitment, social support, and emotional maturity. Obstacles encountered include technical constraints, time differences, and psychological stress due to assignment situations in conflict areas. In conclusion, appropriate, adaptive, and systematic communication strategies play an important role in maintaining family harmony even when physically separated for a long period of time.